Chemoprevention Gene Therapy (CGT) of Pancreatic Cancer Using Perillyl Alcohol and a Novel Chimeric Serotype Cancer Terminator Virus - Sarkar, S.; Azab, B.; Quinn, B.A.; Shen, X.; Dent, P.; Klibanov, A.L.; Emdad, L.; Das, S.K.; Sarkar, D.; Fisher, P.B. (Current Molecular Medicine, 2014)
Conditionally replication competent adenoviruses (Ads) that selectively replicate in cancer cells and simultaneously express a therapeutic cytokine, such as melanoma differentiation associated gene- 7/Interleukin-24 (mda-7/IL-24), a Cancer Terminator Virus (CTV-M7), hold potential for treating human cancers. To enhance the efficacy of the CTV-M7, we generated a chimeric Ad.5 and Ad.3 modified fiber bipartite CTV (Ad.5/3-CTV-M7) that can infect tumor cells in a Coxsackie Adenovirus receptor (CAR) independent manner, while retaining high infectivity in cancer cells containing high CAR. Although mda-7/IL-24 displays broad-spectrum anticancer properties, pancreatic ductal adenocarcinoma (PDAC) cells display an intrinsic resistance to mda-7/IL-24-mediated killing due to an mda-7/IL-24 mRNA translational block. However, using a chemoprevention gene therapy (CGT) approach with perillyl alcohol (POH) and a replication incompetent Ad to deliver mda-7/IL-24 (Ad.mda-7) there is enhanced conversion of mda-7/IL-24 mRNA into protein resulting in pancreatic cancer cell death in vitro and in vivo in nude mice containing human PDAC xenografts. This combination synergistically induces mda-7/IL-24-mediated cancer-specific apoptosis by inhibiting anti-apoptotic Bcl-xL and Bcl-2 protein expression and inducing an endoplasmic reticulum (ER) stress response through induction of BiP/GRP-78, which is most evident in chimeric-modified non-replicating Ad.5/3- mda-7- and CTV-M7-infected PDAC cells. Moreover, Ad.5/3-CTV-M7 in combination with POH sensitizes therapy-resistant MIA PaCa-2 cell lines over-expressing either Bcl-2 or Bcl-xL to mda-7/IL-24-mediated apoptosis. Ad.5/3-CTV-M7 plus POH also exerts a significant antitumor ‘bystander’ effect in vivo suppressing both primary and distant site tumor growth, confirming therapeutic utility of Ad.5/3-CTV-M7 plus POH in PDAC treatment, where all other current treatment strategies in clinical settings show minimal efficacy.
Keywords: chemoprevention gene therapy (CGT)